Features of a Systematic Approach to the Prevention of Healthcare-Associated Infections in the Russian Federation and abroad - M. A. Davydova; G. D. Bryukhanova; V. N. Gorodin (Эпидемиология и вакцинопрофилактика)
Relevance. Health care-associated infections (HAIs) are one of the global problems of modern healthcare with a negative trend in the growth of this pathology throughout the world, which is due to a complex of reasons, among which the resistance of pathogens of hospital infections to antimicrobials is important, as well as gaps in organization of epidemiological surveillance due to a number of objective and subjective factors (complication of technologies and expansion of the practice of invasive medical interventions, turnover and shortage of personnel in medical institutions, etc.).The purpose of the work is to study the experience of organizing measures for the prevention of HCAI from the standpoint of a systematic approach in Russia and in foreign countries that have the best practices in this area. The purpose of the work is to study the experience of organizing measures for the prevention of HCAI from the standpoint of a systematic approach in Russia and in foreign countries that have the best practices in this area.The results are based on the study of the basic principles of the system approach, its tools, functional organization and universalization, the use of a comprehensive analysis in relation to different areas of medical activity and types of medical care, the sequence of development and implementation of new methods in Russian and foreign experience in the implementation of epidemiological surveillance for HCAI. Problems in the field of organization and practical implementation of preventive measures to prevent the occurrence of HCAI have been identified, and urgent tasks for improving the epidemiological safety of medical activity have been identified.Conclusion. Differences were noted in approaches to the prevention of HAIs in Russia and abroad, concerning the resource provision of molecular biological monitoring of HAI pathogens, as well as the features of teamwork, targeted communication in medical teams and in explanatory work, as well as the implementation of training programs for relatives to care for patients with HAI. Measures are proposed to increase the commitment of medical personnel and collectives in general, other employees of medical organizations to epidemiologically safe skills in their professional activities, to develop patient education programs for personal prevention of HCAI.